Frequency and predisposing factors for drug-induced hypoglycemia in patients with type-2 diabetes mellitus - Atiqulla Shariff; Sathvik Belagodu Sridhar; Hana Rami Bittar; Ahed Hamad; Reem Ahmed; Ghaidaa Kadour (Wolters Kluwer Medknow Publications, 2019)
Objective: Hypoglycemia is the most common complication of the treatment for diabetes mellitus. Various factors predispose an individual for drug-induced hypoglycemia. The aim of this study was to explore the relative frequency and likely predisposing factors for drug-induced hypoglycemia among type-2 diabetic patients in the United Arab Emirates (UAE). Methods: In this cross-sectional survey-based study which was conducted from February to April 2018 in two local community pharmacies in the UAE, diabetic patients underwent a structured interview on their diabetes mellitus status and management and specific open-ended questions related to hypoglycemic symptoms that they might have experienced and the occurrence of symptoms. Collected data were used to estimate the relative frequency of drug-induced hypoglycemia and to identify the probable predisposing factors and their contribution in causing hypoglycemia using relative risk, Chi-square test, and Fisher's exact test. Findings: The relative frequency of drug-induced hypoglycemia in our study was 46.25%. Patients' age of ≥65 years, duration of diabetes mellitus for more than 1 year, patients with more than one comorbid condition, and patients using more than one antidiabetic medication were predisposing for developing drug-induced hypoglycemia. Conclusion: The relative frequency of drug-induced hypoglycemia in a nontrial environment which lacks the special cares routinely provided in drug development clinical trials is high. We suggest that more attention should be paid to identify, prevent, and manage drug-induced hypoglycemia in type-2 diabetic patients who have more than 1 year of diabetes, more than one comorbidity, using more than one antidiabetic medication, and elderly.